(untitled) (Research, Society and Development, 2022)
The present work aimed to calculate thermal comfort indexes for broilers facilities at Chimoio city, province of Manica/Mozambique. From average monthly data on air temperature and relative humidity, Temperature and Humidity Index (THI) were calculated for different life stages of the birds. THI showed higher values in summer and lower values in winter. For birds of one week it was observed that every winter is stressful due to the cold, for birds of three weeks winter is of thermal comfort, and for birds of six months, at Chimoio natural environmental conditions, every season is of heat stress.